Optimization Of Progressive Scientific Literacy Based On The Sciedugame Mobile Application On The Topic Of Earth And The Solar System At SMP Negeri 56 Surabaya - Ashdaqofillah, Muhammad Rizky; Widodo, Wahono (Justek : Jurnal Sains dan Teknologi, 2025)
This study aimed to analyze the effect of the Sciedugame Mobile application on the development of students’ progressive scientific literacy in junior high school science learning. A quasi-experimental design was employed with two eighth-grade classes at SMP Negeri 56 Surabaya. The experimental class used the Sciedugame Mobile application, while the control class received conventional instruction. Data were collected through pre-test and post-test assessments, classroom observations, and student questionnaires. The results showed that the experimental group achieved higher learning gains than the control group. The average post-test score in the experimental class was 68.38, compared to 58.48 in the control class. The normalized gain (N-Gain) in the experimental group was 0.49 (moderate), while the control group scored 0.36. A t-test confirmed a significant difference between the two groups (tcount = 1.87 > ttable = 1.67 at α = 0.05). In addition, scientific literacy indicators—such as conceptual understanding, scientific process skills, and real-life application—improved more significantly in the experimental class. Observation results also indicated higher implementation quality in the experimental group (97.44%) compared to the control group (76.92%). Furthermore, student responses toward the application were overwhelmingly positive in terms of usability, content clarity, and engagement. These findings suggest that Sciedugame Mobile is a promising mobile learning tool to support progressive scientific literacy in science education.